Optimalisasi Jiwa Kewirausahaan Guru-Guru Madrasah Aliyah Negeri Kota Mojokerto Melalui Workshop Edupreneurship Berbasis Teknologi Digital - Imam Bukhori; Ludi Wisnu Wardhana; Elfia Nora (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2023)
Entrepreneurship related to education is very much and can be realized by practitioners in the field of education and academics, so that they can transfer their knowledge to students related to entrepreneurship. One way that can be realized by the school is to apply entrepreneurship-based subjects, by instilling the value of an entrepreneurial spirit, and application by inviting students to practice directly in trying entrepreneurship related to Education, including as a reception service for typing proposals or reports, application or web development services, and can also be as an Education tour planner, become content creators, educational institutions, and others. Based on the description of the situation analysis and observations that have been made to the partner place in the implementation of this community service, the partner's problems are formulated as follows: 1) There is still a lack of understanding of teachers and schools about the importance of edupreneurship applied in learning in schools, and there is still a lack of knowledge about the type of eduprenuership, 2) The need to develop knowledge and practice of digital technology-based eduprenuership to teachers in schools. Based on the results of interviews and discussions with partners, to overcome partner problems, the methods that will be implemented in this community service activity are: 1) Providing education about the importance of edupreneurship applied in learning in schools, and still lack knowledge about the type of eduprenuership, 2) Providing assistance and guidance, edupreneurship practices related to digital technology to teachers. The results of this community service are 1) Madrasah Aliyah Negeri Kota Mojokerto teachers can pour creative ideas in entrepreneurship that can be applied by teachers and students in schools and poured into business design, 2) Through the practice and assistance provided, teachers can already practice digital marketing using online applications.